Day-case total hip arthroplasty: a safe and sustainable approach to improve satisfaction and productivity, and meet the needs of the orthopaedic population. Issue 1 (February 2022) - Hall, Andrew J.; Dunstan, Edward
Abstract: The demand for lower limb arthroplasty is projected to increase significantly over the next three decades, which poses a major challenge to healthcare services. Novel solutions in arthroplasty services are required to meet the growing volume of patients that require essential orthopaedic surgery. These solutions must be safe, efficient, and reproducible at scale. They must also be robust to the disruption felt with increasing frequency from the need to accommodate the growth of unscheduled inpatient care services. Day case total hip arthroplasty (THA) has become established in North America and is being used with increasing frequency in the UK and Europe. This approach been shown to be safe and effective in a wide variety of settings and is associated with good outcomes and high levels of patient satisfaction. Day case arthroplasty may improve the efficiency and productivity of planned essential surgery by reducing the burden on inpatient services, and consequently the demand for day case THA is likely to increase. It is therefore essential that the principles of day case THA are included in the continued professional development of clinicians in orthopaedic surgery, anaesthetics and perioperative care, and allied health professionals involved in the delivery of arthroplasty services. The first part of this article offers a narrative review of day case THA and considers the relative merits of this approach to lower limb arthroplasty services. The second part describes the experiences of successful units and provides a summary of the principles that are essential to deliver safe and effective care.